Factorial Structure and Reliability of Cyberbullying Questionnaire (CBQ) and her Complement (BCQ-V) in Ecuadorian Teenagers - Ramos-Noboa, Isabel (2020)
Objective. To analyze the factor structure and reliability of the Cyberbullying Questionnaire (CBQ), which measures the prevalence of cyberbullying; as well as measure the complement on victimization (CBQ-V). Method. The study is instrumental in verifying the factorial construction and internal consistency of the tests in a sample of 998 high school students from six educational centres in Tungurahua. Results. It was found that the CBQ explains 58.5% of the variance with three factors with values ​​of S-B c2= 29.5; df = 24; p > .05; S-B c2/df = 1.2; NNFI = .95; CFI = .96; GFI = .90 and RMSEA = .08 IC 90% [.10 - .05]. While the CBQ-V also with three factors explains 52.6% of the variance with S-B c2 = 29.5; df = 24; p > .05; S-B c2/df = 1.2; NNFI = .95; CFI = .96; GFI = .90 and RMSEA = .08 IC 90% [.10 -.05]. Regarding reliability, the scores reached for the CBQ is α(ordinal)= .903 and CBQ-V is α(ordinal)= .879. It is concluded that the tests under analysis are valid as a construct and reliable in Tungurahua high school students.